Chapter Signorie rurali e risorse economiche: forme di prelievo e di gestione - STENICO, MARCO (Reti Medievali E-Book, 2023)
In the fourteenth and fifteenth centuries, the rural lords exercised strong control over the economic resources of the Trentino area. The essay illustrates the forms of land rent collection, and dwells in particular on the exploitation of mineral resources.